Mobility patterns of docked bikes vs cars in Lisbon: Assessing its impact in air quality during event days - Henriques, Guilherme Lopes (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Business Analytics